2010
DOI: 10.3322/caac.20059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Older Patient with Cancer: Understanding Frailty and the Geriatric Assessment

Abstract: The majority of cancer incidence and mortality occurs in individuals aged older than 65 years, and the number of older adults with cancer is projected to significantly increase secondary to the aging of the US population. As such, understanding the changes accompanying age in the context of the cancer patient is of critical importance. Agerelated changes can impact tolerance of anticancer therapy and can shift the overall risk-benefit ratio of such treatment. A challenge in implementing evidence-based approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(63 citation statements)
references
References 124 publications
(127 reference statements)
1
61
0
Order By: Relevance
“…Regression analysis revealed that function scores were likely to be lower for older patients. This is contradictory to findings by Van Cleave and colleagues, who investigated only those aged 65 or more and did not find an association between chronological age and functional status [25]. They did, however, find that an increased number of comorbidities were associated with reduced functional status.…”
Section: Discussionmentioning
confidence: 59%
“…Regression analysis revealed that function scores were likely to be lower for older patients. This is contradictory to findings by Van Cleave and colleagues, who investigated only those aged 65 or more and did not find an association between chronological age and functional status [25]. They did, however, find that an increased number of comorbidities were associated with reduced functional status.…”
Section: Discussionmentioning
confidence: 59%
“…If the projections in population shifts prove correct and no mitigating interventions are developed, these numbers are just going to get worse. Compounding these issues is a shift in the risk-benefit ratio of anticancer therapeutics due to age-related changes that impact their tolerance [7]. Added to that is an underrepresentation of this demographic in clinical trials designed to evaluate potential therapies [7].…”
Section: The Problemmentioning
confidence: 99%
“…Compounding these issues is a shift in the risk-benefit ratio of anticancer therapeutics due to age-related changes that impact their tolerance [7]. Added to that is an underrepresentation of this demographic in clinical trials designed to evaluate potential therapies [7]. A central question is whether or not slowing the process of aging in human populations a) prevents and/or delays the development, growth and/or progression of cancer; b) improves patient's tolerance for anticancer therapeutics.…”
Section: The Problemmentioning
confidence: 99%
“…Polypharmacy is a significant risk factor for functional deterioration and poor outcomes in elderly patients and a risk factor for increased morbidity and mortality. 14 Vitamin D deficiency has been associated with frailty syndrome. A study of 444 male and 561 female participants aged 65 years and older from the Inchanti study Shardell et al 15 found that vitamin D insufficiency was associated with frailty only in men.…”
Section: Introductionmentioning
confidence: 99%